Managers' Perceptions of Learning in New Product Development - Koners, Ursula; Goffin, Keith (Emerald Group Publishing Limited, 2007)
Companies need to ensure that each and every new product development (NPD) project results in not only a successful new product but also generates learning for the organization. Post-project reviews (PPRs) are widely recommended as an appropriate mechanism to stimulate project-toproject learning in NPD teams. Surprisingly, empirical research on their potential to support learning in NPD is limited. This paper describes an investigation of how NPD personnel perceive the utility of PPRs and of their potential to create tacit knowledge. It is part of an intensive exploratory study of five companies, using a multi-facetted case study methodology. The results indicate that NPD personnel perceive PPRs to be a useful mechanism and also that social interactions and tacit knowledge seem to play key roles in NPD learning. For operations management researchers interested in product development, the study furthers our understanding of learning in NPD, indicates topics that need further investigation, and suggests suitable methodologies. For practitioners, the results indicate the potential for more effective team learning in NPD.
Keywords: New products; Project evaluation; Project management